Burden-of-illness and cost-driving factors in Dravet syndrome patients and carers: A prospective, multicenter study from Germany. (May 2019) - Strzelczyk, Adam; Kalski, Malin; Bast, Thomas; Wiemer-Kruel, Adelheid; Bettendorf, Ulrich; Kay, Lara; Kieslich, Matthias; Kluger, Gerhard; Kurlemann, Gerhard; Mayer, Thomas; Neubauer, Bernd A.; Polster, Tilman; et al.
Abstract: Introduction: Dravet syndrome (DS) is a rare developmental and epileptic encephalopathy. This study estimated cost, cost-driving factors and quality of life (QoL) in patients with Dravet syndrome and their caregivers in a prospective, multicenter study in Germany. Methods: A validated 3–12-month retrospective questionnaire and a prospective 3-month diary assessing clinical characteristics, QoL, and direct, indirect and out-of-pocket (OOP) costs were administered to caregivers of patients with DS throughout Germany. Results: Caregivers of 93 patients (mean age 10.1 years, ±7.1, range 15 months–33.7 years) submitted questionnaires and 77 prospective diaries. The majority of patients (95%) experienced at least one seizure during the previous 12 months and 77% a status epilepticus (SE) at least once in their lives. Over 70% of patients had behavioural problems and delayed speech development and over 80% attention deficit symptoms and disturbance of motor skills and movement coordination. Patient QoL was lower than in the general population and 45% of caregivers had some form of depressive symptoms. Direct health care costs per three months were a mean of €6, 043 ± €5, 825 (median €4054, CI €4935-€7350) per patient. Inpatient costs formed the single most important cost category (28%, €1, 702 ± €4, 315), followed by care grade benefits (19%, €1, 130 ± €805), anti-epileptic drug (AED) costs (15%, €892 ± €1, 017) and ancillary treatments (9%, €559 ± €503). Total indirect costs were €4, 399 ±€ 4, 989 (median €0, CI €3466-€5551) in mothers and €391 ± €1, 352 (median €0, CI €195-€841) in fathers. In univariate analysis seizure frequency, experience of SE, nursing care level and severe additional symptoms were found to be associated with total direct healthcare costs. Severe additional symptoms was the single independently significant explanatory factor in a multivariate analysis. Conclusions: This study over a period up to 15 months revealed substantial direct and indirect healthcare costs of DS in Germany and highlights the relatively low patient and caregiver QoL compared with the general population. Highlights: First study to measure the socio-economic impact of Dravet syndrome over a period up to 15 months. Patients had a range of comorbidities, many of which caregivers rated as severely problematic. Mean direct costs were estimated at €6, 666 and indirect costs at €4, 790 over three months. Total cost is driven by the number of additional symptoms rated by carers as severe. Patient QoL is lower compared to the general population, and 45% of caregivers experienced some form of depressive symptoms.